Interventions for treating obstetric fistula: An evidence gap map. - Eugenie Evelynne Johnson; Nicole O'Connor; Paul Hilton; Fiona Pearson; Judith Goh; Luke Vale (Public Library of Science (PLoS), 2023)
Obstetric fistula is prevalent in low- and middle-income countries, with between 50,000 and 100,000 new cases each year. The World Health Organization aims to eradicate it by 2030 but a clear idea of the extant evidence is unavailable. This evidence map compiled evidence on treatments for obstetric fistula to identify potential knowledge gaps. The protocol for this work was published on the Open Science Framework (DOI: 10.17605/OSF.IO/H7J35). A survey was developed, piloted and distributed online through organisations with an interest in obstetric fistula and snowballing. Results informed the evidence map framework. Searches were run on MEDLINE, Embase, CENTRAL, Global Index Medicus and ScanMedicine on 16 February 2022 to identify potentially eligible systematic reviews, randomised controlled trials, cohort studies and case-control studies. Forward and backward citation chaining was undertaken on relevant systematic reviews and included studies. Studies were screened, coded and assessed for risk of bias by a single reviewer, with a second checking a proportion. The evidence map results were compared to survey results. Thirty-nine people responded to the survey, half of which were clinicians. Of 9796 records identified, 37 reports of 28 studies were included in the evidence map. Many included studies were at some risk of bias; for observational studies, this was predominantly due to lack of controlling for confounders. Most studies (71%) assessed surgical interventions alone. Reporting on other intervention types was limited. Regarding outcome measures most important to survey respondents, 24 studies reported on cure/improvement in obstetric fistula and 20 on cure/improvement in urinary incontinence. Reporting on quality of life, faecal incontinence and sexual function was limited. There is currently little robust evidence to guide patients and practitioners on the most effective treatment option for obstetric fistula. Further research is required to address evidence gaps identified.